Genealogy of a Act. Signatories on the Act of the Extraordinary Cabildo (Council) in Santafé on July the 20th, 1810 - Marín Leoz, Juana María (Pontificia Universidad Javeriana, 2014)
This paper begins with the analysis of the 53 signatories of the Extraordinary Council Minute in Santafé on July the 20th, 1810, with the aim at characterizing and identifying, beyond their names, all the people that signed the Act of Independence santafereña. From the analysis of personal, professional and familiar paths of the signatories, this paper shows different power scenarios and looks forward to the reinterpretation of traditional analysis that highlight the adept at breaking and groundbreaking condition and belief of those who signed the beginning of santafereña transformation in that Friday, july the 20th.